2018
DOI: 10.1002/ajpa.23613
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stability and environmental stress: A geometric morphometrics analysis of asymmetry in the human femur

Abstract: The geometric morphometrics analysis of femoral asymmetry was effective for distinguishing two populations. After considering various factors of influence, genetics and biomechanics seem to have a limited impact on the results. Expressing FA appears to be normal but dependent on the disturbances of DS produced by environmental stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…37 In adults, the long bones of the upper limbs are usually larger (diaphyseal width and length) on the right side, but in the lower limbs, bones are larger on the opposite left side, most noticeable in the femur. 28,38,39 There are a limited number of reports 29,30,40,41 that are sometimes contradictory with respect to bone asymmetries in equine hindlimbs. Previous studies reported that many femoral parameters were larger in the right hind limb of adult racehorses, 40 and longer third metatarsals, and larger tarsocrural joints were also measured in the right limbs of adult mixed breed horses.…”
Section: Limb Directional Asymmetry Is Present In the Stifles Of Heal...mentioning
confidence: 99%
“…37 In adults, the long bones of the upper limbs are usually larger (diaphyseal width and length) on the right side, but in the lower limbs, bones are larger on the opposite left side, most noticeable in the femur. 28,38,39 There are a limited number of reports 29,30,40,41 that are sometimes contradictory with respect to bone asymmetries in equine hindlimbs. Previous studies reported that many femoral parameters were larger in the right hind limb of adult racehorses, 40 and longer third metatarsals, and larger tarsocrural joints were also measured in the right limbs of adult mixed breed horses.…”
Section: Limb Directional Asymmetry Is Present In the Stifles Of Heal...mentioning
confidence: 99%
“…Given that morphology is considered one of the most conspicuous facets of the phenotype, reflecting the complex nexus between structural elements and biological functions within organs and tissues, it is asymmetry that emerges as an indicator signaling the presence of disorders. Thus, it can be regarded as a phenotypic effect of developmental instability [10,21,36].…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuating asymmetry describes deviations from an organism's bilaterally symmetrical body plan (Palmer & Strobeck, 1986 ; Van Valen, 1962 ), and can be used as a biomarker of developmental instability and environmental stress (Beasley et al, 2013 ; McGrath et al, 2022 ; Møller & Thornhill, 1997 ; Van Dongen, 2006 ; Van Dongen & Gangestad, 2011 ). Fluctuating asymmetry has been studied in humans—both on modern and archeological populations and on the cranium and the post‐cranial skeleton (Bigoni et al, 2013 ; Chovalopoulou, Papageorgopoulou, & Bertsatos, 2017 ; DeLeon, 2007 ; Gawlikowska et al, 2007 ; Gawlikowska‐Sroka et al, 2017 ; Mopin et al, 2018 ; Zurawiecka et al, 2019 ). Studying fluctuating asymmetry can be difficult since it is generally a small biological signal and is, therefore, vulnerable to measuring error (Greene, 1984 ; Lundström, 1960 ; Palmer & Strobeck, 1986 ).…”
Section: Introductionmentioning
confidence: 99%